An Entropy Weight-TOPSIS Based Method for e-Commerce Logistics Service Quality Evaluation - Lihong Wang; Manpei Dong (Tehnički Vjesnik, 2023)
The problem of logistics service quality is the weakness that restricts the high-quality development of rural e-commerce. The paper combines SERVQUAL model and LSQ scale to build a rural e-commerce logistics evaluation system with five first-level indicators of reliability, timeliness, convenience, economy and empathy and 18 second-level indicators. On this basis, the service quality of five typical rural e-commerce logistics enterprises is comprehensively evaluated by using the entropy weight method and TOPSIS method through a questionnaire survey. The results show that the quality of logistics service should be improved from reliability and empathy. The service quality of Enterprise 4 is the highest, and that of Enterprise 5 is the worst.